2015
DOI: 10.1136/bmj.h2698
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine prescribing patterns and deaths from drug overdose among US veterans receiving opioid analgesics: case-cohort study

Abstract: ObjeCtiveTo study the association between benzodiazepine prescribing patterns including dose, type, and dosing schedule and the risk of death from drug overdose among US veterans receiving opioid analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
394
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(417 citation statements)
references
References 30 publications
14
394
3
6
Order By: Relevance
“…For example, half of all opioidrelated deaths also involved a benzodiazepine, 18% involved antihistamines, and 9% involved a tricyclic antidepressant. Not only does this suggest a high level of mental health comorbidity in this population, but given the body of research confirming a clinically important interaction between opioids and CNS depressants 10,11 , these findings are of considerable concern. In particular, this suggests that dangerous combinations of medications contribute frequently to accidental fatal opioid overdoses.…”
Section: Opioid Involvementmentioning
confidence: 95%
“…For example, half of all opioidrelated deaths also involved a benzodiazepine, 18% involved antihistamines, and 9% involved a tricyclic antidepressant. Not only does this suggest a high level of mental health comorbidity in this population, but given the body of research confirming a clinically important interaction between opioids and CNS depressants 10,11 , these findings are of considerable concern. In particular, this suggests that dangerous combinations of medications contribute frequently to accidental fatal opioid overdoses.…”
Section: Opioid Involvementmentioning
confidence: 95%
“…(2) Consistency is the strongest evidence, with 33 of 34 studies showing a positive association of hypnotic consumption and mortality. (3) Several kinds of specificity of hypnotics-mortality associations have been identified: the excess of deaths at night among hypnotics users [21], the excesses of infection [13], COPD [57], and suicide deaths [50], and the excess of specific cancers such as lung and esophagus [38]. (4) The temporality of hypnotic usage preceding death is consistent with causation.…”
Section: Bradford Hill Criteria Of Causation Are Fulfilledmentioning
confidence: 99%
“…For these applications, the mechanisms by which hypnotics hyperpolarize and inhibit respiratory neurons leading to death are well understood at the molecular, cellular, physiologic and organismic levels. Also reported are thousands of overdose deaths per year attributable to hypnotics, with a larger number of cases in which hypnotics as well as opiates and other sedatives are lethal in combination [50][51][52]. It has been suggested that currently, tens of thousands of yearly self-injury deaths are related to hypnotics and sedative use [53].…”
Section: The Causality Of Hypnotics Effects On Mortalitymentioning
confidence: 99%
“…[9][10][11][12][13][14][15]33 However, concomitant opioids and sedatives have been prescribed in our clinic at a proportion (43.6%) greater than recommended by guidelines, possibly enhancing overdose risk. 10,30,34,35 We presently are modifying these regimens.…”
Section: Discussionmentioning
confidence: 99%